Comparative evaluation of the gestosis score and uterine artery pulsatility index for predicting gestational hypertension: a prospective observational study - Thakkannavar, Jyoti; Jakhar, Rekha; Chaudhary, Vimla; Chaudhary, Ankita; Rani, Nishu (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Hypertensive disorders of pregnancy (HDP) are a leading cause of maternal and perinatal morbidity, with gestational hypertension (GH) often posing diagnostic and prognostic challenges. Early identification of at-risk women is essential, particularly in resource-limited settings. The HDP-gestosis score and uterine artery pulsatility index (UtA-PI) have been proposed as potential screening tools for GH, but their predictive value requires further validation. Methods: This prospective observational study was conducted at a tertiary care hospital in Jodhpur, India, including 140 pregnancies between 11 to 14 weeks of gestation. Baseline demographic, clinical, and obstetric details were recorded. Each participant underwent gestosis score calculation using a standardized application and bilateral uterine artery Doppler for UtA-PI measurement. Women were followed until delivery, and the development of GH, as defined by ACOG criteria, was documented. Results: The mean gestosis score was significantly lower in women who subsequently developed GH compared to normotensive women (2.59±1.76 vs. 3.55±1.73; p=0.019), suggesting limited predictive consistency in this cohort. Mean UtA-PI was higher among women with GH (1.61±0.57 vs. 1.46±0.57), though this difference did not reach statistical significance (p=0.263). Conclusions: Neither the gestosis score nor UtA-PI demonstrated robust standalone predictive performance for GH in this population. These findings highlight the need for contextual calibration of existing tools and suggest that multimodal approaches, combining clinical, biophysical, and biochemical parameters, may be more effective. Integration of validated scoring systems into routine antenatal surveillance could strengthen risk stratification, facilitate timely interventions, and improve maternal and perinatal outcomes.